DISPARITAS PENJATUHAN HUKUMAN PIDANA DALAM PERKARA KEKERASAN FISIK DALAM RUMAH TANGGA YANG DILAKUKAN SUAMI TERHADAP ISTRI DI PENGADILAN NEGERI JAMBI - Suzanalisa Suzanalisa (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
This study aims to determine and analyze the effectiveness of Law Number 23 Year 2004 in the settlement of cases of domestic violence in the jurisdiction of Jambi City and explain the concept of reform Law No. 23 of 2004 in solving cases of domestic violence in the jurisdiction of the city of Jambi. This research uses "Juridical Empirical" method of studying the existing legislation and then connected with the implementation of Law Number 23 Year 2004 in the settlement of cases of domestic violence in the jurisdiction of Jambi City in the criminal justice system. The result of the research was obtained 1. Not yet effective Law Number 23 Year 2004 in the settlement of cases of domestic violence in jambi city law is influenced by law enforcement factors that is the benchmark of legal effectiveness is The existence of weaknesses in Law Number 23 Year 2004, Lack of understanding and lack of coordination between institutions that are obliged to provide services to victims of Domestic Violence, Lack of safe and convenient facilities for victims to tell the psychological trauma experienced so that from various explanations of the victims to be input to law enforcement, Still an opinion that assumes Domestic Violence is a non-criminal family affair that can be resolved by law. 2. The concept of renewal of Law Number 23 Year 2004 in resolving cases of domestic violence in the jurisdiction of the City of Jambi namely a. amendment of Law Number 23 Year 2004 with regard to the relationship of roles and responsibilities of the State in facing the domestic violence problem between husband and wife in Indonesia as well as the interests of the people around the victims, especially the children of the marriage and still accommodate the difference religious law that applies to every adherent and socio-cultural values of society; b. The need of the victim (perspective) perspective in solving the problem of Domestic Violence is that the victim is placed as the main actor not as a complement which is only confessed. c. the existence of structural alignment in each subsystem of criminal justice system that is Police, Prosecutor, Courts and Penitentiary also in functional relationship in an integrated manner by considering the necessity and interest of victim by referring to gender fair values become the basis of effort of fostering of Criminal Justice System gender equality. Recommendations submitted are 1. To hasten the amendment (amendment) of Law Number 23 Year 2004; 2. To immediately implement a gender justice criminal justice system in providing protection and enforcement of human rights, gender equity and justice, protection of victims, non-discrimination principle; 3. an increase in the number of law enforcement officers ranging from police, prosecutors, judges, lawyers who have gender equality principles as well as to prisons in fostering perpetrators in prisons; 4. improving the quality of law enforcers through gender-based seminars, gender-based exercises, to obtain the desired impression of law enforcement through the criminal justice system as a forum for obtaining justice and legal certainty.Keywords: Effectiveness of Law Number 23 Year 2004, Domestic Violence, The Concept of Renewal